Treatment of Depression and PTSD in Primary Care Clinics Serving Uninsured Low-Income Mostly Latina/o Immigrants: A Naturalistic Prospective Evaluation - Kaltman, Stacey (Cultur Divers Ethnic Minor Psychol, 2019)
OBJECTIVES: Uninsured immigrants to the US are psychologically vulnerable due to limited access to mental health services. Latina/o immigrants from Central and South America are further at risk due to high levels of trauma exposure, both in their country of origin and adopted country. Effective behavioral interventions in primary care are needed to address this services gap for common trauma-related mental disorders, including depression and posttraumatic stress disorder (PTSD). A naturalistic prospective study compared depression and PTSD outcomes for uninsured primary care patients, mostly Latina/o immigrants, in clinics with distinct models for integrating behavioral health services. One clinic had a collaborative care program, i.e., a multi-component, system-level intervention with the goals of facilitating increased screening, improving accuracy, increasing uptake of evidence-based treatment, and utilizing measurement-based treatment to target. The other had co-located services, with an on-site therapist. METHOD: One hundred thirty-eight patients with presumptive depression were interviewed at baseline. Follow-up data were collected 8-months later. Care received between the two assessments was ascertained by chart review. RESULTS: There was a significant decrease in depression symptoms regardless of clinic. Factors associated with improved depression outcomes included absence of comorbid PTSD and lack of additional trauma exposures. Although there was overall improvement in PTSD, there was significantly more improvement in the collaborative care clinic. CONCLUSIONS: Results suggest that both models were effective for depression and PTSD; however, the collaborative care model had added benefits for those patients with PTSD.